Local and regional trends in Plio‐Pleistocene δ18O records from benthic foraminifera. (20th August 2014) - Bell, David B.; Jung, Simon J. A.; Kroon, Dick; Lourens, Lucas J.; Hodell, David A.
Abstract We present new orbital‐resolution Pliocene‐Pleistocene benthic stable oxygen isotope (δ18Ob) records from Ocean Drilling Program Sites 1264 and 1267, from Walvis Ridge in the Southeast Atlantic. We compare long‐term (>250 kyr) interbasin δ18Ob‐gradients between Pacific and North Atlantic regional stacks, as well as intra and interbasin gradients from the perspective of Walvis Ridge. The δ18Ob values from Sites 1264 and 1267 are almost always higher than deep North Atlantic and Pacific sites, with large gradients (>0.5‰) emerging abruptly at ∼2.4 Ma and persisting until ∼1.3 Ma. From this, we infer the presence of a new water mass, which resulted from the influence of dense, 18O‐enriched Nordic sea overflow waters via the abyssal East Atlantic. Meanwhile, long‐term average δ18Ob values in the North Atlantic appear to have remained within 0–0.25‰ lower than in the Pacific. However, the magnitude of this difference is sensitive to the inclusion of records from the equatorial West Atlantic. These results, together with constraints based on temperature, salinity, and density, suggest an influence of the seawater δ18O (δ18OSW) versus salinity relationship of source waters on δ18Ob values within the Atlantic. In particular, the abrupt emergence at ∼2.4 Ma of higher δ18Ob values at Sites 1264 and 1267, relative to North Atlantic records, appears to require a low‐latitude surface water δ18OSW signal. This implies a connection between northward heat transport and deep water export into the abyssal East Atlantic. Hence, our results have implications for the interpretation of δ18Ob records and highlight the potential for δ18Ob to constrain deep Atlantic water mass sources and pathways during the Plio‐Pleistocene.